Antarctica A Key To Global Change - Kanao, Masaki; Toyokuni, Genti; Yamamoto, Masa-yuki (IntechOpen, 2019)
The most exciting initiative in the polar region was the International Polar Year (IPY) in 2007-2008, conducted as the 50th anniversary of the International Geophysical Year (1957-1958). The initiative greatly enhanced the exchange of ideas across nations and scientific disciplines to unveil the status and changes of planet Earth. This sort of interdisciplinary exchange helps us to understand and address grand challenges, such as rapid environmental change and its impact on society. In this regard, this book aims to compile the achievements of projects related to the IPY and post-IPY era, focusing especially on surface environmental variations associated with climate change, such as global warming.